Proportional Assist Ventilation Improves Leg Muscle Reoxygenation After Exercise in Heart Failure With Reduced Ejection Fraction - Borghi-Silva, Audrey; Goulart, Cassia da Luz; Carrascosa, Cláudia R.; Oliveira, Cristino Carneiro; Berton, Danilo C.; de Almeida, Dirceu Rodrigues; Nery, Luiz Eduardo; Arena, Ross; Neder, J. Alberto (Frontiers in Physiology, 2021)
Background Respiratory muscle unloading through proportional assist ventilation (PAV) may enhance leg oxygen delivery, thereby speeding off-exercise oxygen uptake (V.⁢O2) kinetics in patients with heart failure with reduced left ventricular ejection fraction (HFrEF). Methods Ten male patients (HFrEF = 26 ± 9%, age 50 ± 13 years, and body mass index 25 ± 3 kg m2) underwent two constant work rate tests at 80% peak of maximal cardiopulmonary exercise test to tolerance under PAV and sham ventilation. Post-exercise kinetics of V.⁢O2, vastus lateralis deoxyhemoglobin ([deoxy-Hb + Mb]) by near-infrared spectroscopy, and cardiac output (QT) by impedance cardiography were assessed. Results PAV prolonged exercise tolerance compared with sham (587 ± 390 s vs. 444 ± 296 s, respectively; p = 0.01). PAV significantly accelerated V.⁢O2 recovery (τ = 56 ± 22 s vs. 77 ± 42 s; p < 0.05), being associated with a faster decline in Δ[deoxy-Hb + Mb] and QT compared with sham (τ = 31 ± 19 s vs. 42 ± 22 s and 39 ± 22 s vs. 78 ± 46 s, p < 0.05). Faster off-exercise decrease in QT with PAV was related to longer exercise duration (r = −0.76; p < 0.05). Conclusion PAV accelerates the recovery of central hemodynamics and muscle oxygenation in HFrEF. These beneficial effects might prove useful to improve the tolerance to repeated exercise during cardiac rehabilitation.